Exploring the Medicinal Potential of Blumea balsamifera: Insights from Molecular Docking and Molecular Dynamics Simulations Analyses - Maulydia, Nur Balqis; Khairan, Khairan; Tallei, Trina Ekawati; Salaswati, Salaswati; Musdalifah, Annisa; Nabila, Fiki Farah; Idroes, Rinaldi (Heca Sentra Analitika, 2024)
Blumea balsamifera from the Ie-Jue geothermal area in Aceh Province, Indonesia, has been reported to have a variety of secondary metabolites. However, there is limited information about the activity of these chemical metabolites from B. balsamifera. The aim of this study is to evaluate the therapeutic potential of these compounds using molecular docking and molecular dynamics simulations. Six selective compounds were thoroughly evaluated using molecular docking techniques for their inhibitory effects on both Coronavirus protease and human interleukin receptors. Additionally, druglikeness assessments based on the Lipinski rule of five were performed to evaluate these six ligands. Our results show that stigmasterol, a key component of B. balsamifera, has demonstrated low binding free energy values across four receptors. Furthermore, molecular dynamics simulations confirmed the stability of the top ligand-receptor complex, particularly stigmasterol-1IRA, based on five parameters, indicating its stability as an inhibitor. This research highlights the potential of stigmasterol as a therapeutic agent derived from medicinal plants of B. balsamifera and underscores the value of our molecular approach in identifying opportunities for pharmaceutical development.